Peri-Myocardial Infarction Pericarditis After Single Stent Early PCI on a STEMI Patient: A Rare Case of Outpatient in Urban Setting - Laksono, Sidhi; Jusuf, Axel (Universitas Ahmad Dahlan, 2024)
Peri-Myocardial Infarction Pericarditis (PMIP), can occur a few days following a myocardial infarction (MI). PMIP frequently exhibits the auscultatory findings of a pericardial friction rub and pericardial effusion. On the other hand, relatively little is known about the management approach. This study aims to report a patient with PMIP following successful revascularization via Percutaneous Coronary Intervention (PCI) for a recent MI. A 50-year-old male was brought to our Outpatient Clinic with chest pain of two days onset. The patient experienced radiating chest pain, cold sweat, heartburn, and general fatigue. ECG shows extensive anterior ST-elevation myocardial infarction (STEMI), and Troponin T was elevated >2000 ng/L. The patient underwent PCI with single stent deployment. Three days later, the patient experienced dyspnea with Transthoracic Echocardiography (TTE) findings consistent with Early PMIP. The patient was discharged after completing full conservative therapy with good results. The clinical findings of PMIP alone may be subtle and go unnoticed. Clinicians should maintain a high level of suspicion in the era of revascularization and develop a strategic plan for timely diagnosis and management. While anti-inflammatory medical therapy is aimed at reducing inflammation and preventing recurrences and progression of the disease, further research is needed to establish prognostic significance and management strategy since clinically diagnosed PMIP has a benign and self-limiting nature.